Hydrogen inhibits cytotrophoblast cells apoptosis in hypertensive disorders complicating pregnancy - Guo, L; Guan, Z; Li, H; Yang, X (Cellular and Molecular Biology, 2016)
Hypertensive disorders complicating pregnancy (HDCP) is one of the most serious medical disorders during pregnancy. Hydrogen is a therapeutic antioxidant and used to treat HDCP effectively. However, the molecular mechanism about the effect of hydrogen on HDCP still remains unclear. In this study, we found ROS content in HDCP group was significantly higher than that in the control and was reduced markedly in the presence of 100Î¼mol/L hydrogen. IL6, Caspase3, Bax1, P-JAK2, P-Stat3 and P-p38 expression was much higher than the control, and was notably decreasedby the application of 100Î¼mol/L hydrogen. Bcl2 expression in HDCP group was notably lower than the control and was increased by 100 Î¼mol/L hydrogen. The apoptosis rate of cytotrophoblast cells was decreased, andratio of cytotrophoblast cells at G1 and G2 phase was increased and decreased by hydrogen, respectively. All those data indicated a potential molecular mechanism of hydrogen-mediated treatment in HDCP.